Supportive care in patients with cancer during the COVID-19 pandemic - Aapro, M. (ESMO Open, 2020)
Cancer care has been profoundly impacted by the global pandemic of severe acute respiratory syndrome coronavirus 2 disease (coronavirus disease 2019, COVID-19), resulting in unprecedented challenges. Supportive care is an essential component of cancer treatment, seeking to prevent and manage chemotherapy complications such as febrile neutropenia, anaemia, thrombocytopenia/bleeding, thromboembolic events and nausea/vomiting, all of which are common causes of hospitalisation. These adverse events are an essential consideration under routine patient management, but particularly so during a pandemic, a setting in which clinicians aim to minimise patients' risk of infection and need for hospital visits. Professional medical oncology societies have been providing updated guidelines to support health care professionals with the management, treatment and supportive care needs of their patients with cancer under the threat of COVID-19. This paper aims to review the recommendations made by the most prominent medical oncology societies for devising and modifying supportive care strategies during the pandemic.